ANALISIS KINERJA KEUANGAN PADA PEMERINTAH DAERAH KABUPATEN LEMBATA TAHUN ANGGARAN 2013-2017 (Studi kaus pada Kantor Badan Keuangan Daerah Kabupaten Lembata) - Asmiyati Atapuka; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to determine the regional financial performance of the Lembata district government in 2013-2017. The results of the study show that in general the financial performance of the district government is good. This is shown by the low average degree of decentralization, the very high regional financial dependency ratio, the regional financial independence ratio is still low with an intructive pattern, the effectiveness of the local tax ratio is quite efficient, the local tax efficiency ratio is efficient, the efficiency expenditure ratio, operating expenditure ratio the total expenditure dominates the expenditure allocation compared to the capital expenditure ratio to total expenditure, the ratio of local revenue growth and the ratio of income growth to positive growth, the ratio of operating expenditure growth, and the capital expenditure growth ratio experiencing positive growth.Keywords: Financial Performance, Financial Ratio, Growth Ratio